AGRICULTURAL DEVELOPMENT OF NIS DEPENDENT UPON SECURE ENERGY SUPPLY - Petrović, Jelena; Dimitrijević, Žarko (Economics of Agriculture, 2012)
In order to achieve energy stability and sustainable development, it is necessary to secure the energy supply and improve efficiency of energy production and consumption at all levels. The increase of energy production from renewable sources will help deliver secure supply and can be one of the most attractive areas for foreign investment in the territory of Niš. Biomass, which is considered to be the greatest potential renewable source of energy in the city of Nis, has insufficiently been utilised. The authors of the paper highlight the importance of using biomass and consider the issues which arise from substituting conventional energies, such as securing the safety of energy supply, enhanced agricultural development and environment protection.